Mitis dan Ontologi sebagai Kekayaan Kajian Seni Tari - Hasprina Resmaniar Boru Mangoensong; Setyo Yanuartuti (Universitas Negeri Medan, 2020)
Human has their own way to resolve their life problem and to adapt with their environment according to their knowledge and culture. People's culture with mythical paradigm about tales and myths are often used as life guidance that need to be applied. They blend themselves in environment and actualize it in ritual and arts. Society with ontology paradigm consider myths as an entertainment, not to be applied in life. They lean on science to explain anything in life, also in arts. These two paradigms spread in some area, villagers and urban society. This distinction of perception produce an argue over which culture and arts are better. Based on this issue, this article aims to inspire mythical community and ontology to use experience capital, knowledge, thoughts, and their culture as substance to study art, to be specific dance art. Each culture has the same material, the only thing that differentiate is the form which is not realized by the community.Also in arts, whether it involves feel or using scientific techniques can be regarded as the property of arts studies.